Real-time forecasting and political stock market anomalies: evidence for the U.S. - Martin T. Bohl; Jörg Döpke; Christian Pierdzioch (Deutsche Bundesbank, 2006)
Using monthly data for the period 1953-2003, we apply a real-time modeling approach to investigate the implications of U.S. political stock market anomalies for forecasting excess stock returns. Our empirical findings show that political variables, selected on the basis of widely used model selection criteria, are often included in real-time forecasting models. However, they do not contribute to systematically improving the performance of simple trading rules. For this reason, political stock market anomalies are not necessarily an indication of market inefficiency.
Keywords: G14; G11; 330; Political stock market anomalies; predictability of stock returns; efficient markets hypothesis; real-time forecasting; Börsenkurs; Kapitalertrag; Prognose; Politische Partei; Effizienzmarktthese; USA